Peran Kepala Sekolah dalam Meningkatkan Kedisplinan Siswa Kelas XI di SMA Kristen Palangka Raya - Wihelmina Everdina Mandibondibo; Sanasintani Sanasintani; Fernando Dorothius Pongoh (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Student discipline is one of the key indicators of a school’s success in shaping character and creating a conducive learning environment. Discipline not only reflects compliance with school regulations but also demonstrates responsibility, honesty, orderliness, and self-control as part of character building. However, in practice, various disciplinary violations are still frequently found among students, such as lateness, failure to complete assignments, truancy, and noncompliance with school dress codes. These issues are also evident at SMA Kristen Palangka Raya, particularly among Grade XI students. Therefore, the role of the school principal as an educational leader is essential in implementing effective strategies to improve student discipline. This study aims to describe the role of the principal in enhancing student discipline among Grade XI students at SMA Kristen Palangka Raya. The research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The participants included the principal, vice principal for student affairs, teachers, and students. The findings revealed that the principal performs several roles: (1) educator, by integrating discipline values through learning activities and character-building programs; (2) manager, by organizing, planning, and implementing school regulations; (3) supervisor, by monitoring and evaluating student discipline; (4) leader, by providing direction and exemplary behavior; and (5) motivator, by giving appreciation and educational sanctions. Challenges encountered include students’ low awareness of discipline and lack of parental involvement. To overcome these obstacles, the principal builds stronger communication with parents, enforces school rules consistently, and conducts continuous character development programs.